Biogenic amine testing in the South African public health care system - D. Legg-E’Silva; E.M. Cave; T. Snyman; S. Currin; N. Kone; K.L. Prigge (Practical Laboratory Medicine)
Background: Phaeochromocytoma, paraganglioma and neuroblastoma are catecholamine secreting neuroendocrine tumours. Biochemical screening for suspected cases of these tumours involves the measurement of catecholamines and their metabolites in either urine or plasma. The South African National Health Laboratory service (NHLS) measures urine fractionated metanephrines (UMF) and normetanephrines (UNF), urine vanillylmandelic acid (UVMA) and urine homovanillic acid (UHVA). Objectives: To analyse the demographic, biochemical and testing patterns of patients’ UMF, UNF, UVMA and UHVA in the NHLS. Methods: Data from January 2015 to December 2016 for all patients undergoing UMF, UNF, UVMA and UHVA testing was extracted from the NHLS central data warehouse. Neuroendocrine tumours were biochemically diagnosed when results were >2x multiples of the upper reference limits. Multiple testing was defined as ≥2 tests within a 14-day period. Ethnicity was determined through hot-deck imputation. Results: Biochemically abnormal test results were identified by UMF/UNF measurements in 98.2 % of cases. In 1.8 % of cases, the addition of UVMA resulted in a previously unidentified biochemical positive. Adult white and coloured populations have significantly less biochemically positive UMF results compared to the African population. Multiple testing resulted in discordant results for 12.8 % of UMF and 13.1 % of UNF testing. Conclusion: UVMA testing for phaeochromocytoma and paraganglioma offers little benefit over testing with UMF alone. Requesting consecutive multiple samples is preferred, however, a single 24-h fractionated UMF/UNF is efficient and cost-effective for phaeochromocytoma and paraganglioma screening, with further testing recommended when clinically indicated. African individuals are more likely to have raised catecholamines and requires further investigation.